Dynamic Performance Analysis of UAV Main Reducer - Zhao Han; Wu Guanhong; Huang Kang; Wu Zhanyu (Jixie chuandong)
Aiming at the a UAV experience complicated dynamics environment under different conditions,firstly,the modal analysis of stress stiffening effect on the UAV main reducer is carried out,the natural frequency and mode shapes are obtained in different conditions.Then frequency response analysis of main reducer is carried out based on certain incentives implementing on the reducer.The research results show that the vibration modes of UAV are mainly torsion and modal natural frequency of UAV main reducer is increased with speed increasing.Through the frequency response analysis,the weak links of the main reducer structure design is predicted,some design references for the main reducer structural optimization are provided.